2015
DOI: 10.1007/s10653-015-9781-1
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons (PAHs) in multimedia environment of Heshan coal district, Guangxi: distribution, source diagnosis and health risk assessment

Abstract: Mining activities are among the major culprits of the wide occurrences of soil and water pollution by PAHs in coal district, which have resulted in ecological fragilities and health risk for local residents. Sixteen PAHs in multimedia environment from the Heshan coal district of Guangxi, South China, were measured, aiming to investigate the contamination level, distribution and possible sources and to estimate the potential health risks of PAHs. The average concentrations of 16 PAHs in the coal, coal gangue, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…The real risk values may otherwise be underestimated. In many urban areas of China, various local emission sources would contribute more polycyclic aromatic hydrocarbons, which increase the lung cancer risks and the health risk was relative high in these regions (Li et al, 2013;Liu et al, 2015;Huang et al, 2016). Therefore, further health risk assessment needs to be done in urban areas.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…The real risk values may otherwise be underestimated. In many urban areas of China, various local emission sources would contribute more polycyclic aromatic hydrocarbons, which increase the lung cancer risks and the health risk was relative high in these regions (Li et al, 2013;Liu et al, 2015;Huang et al, 2016). Therefore, further health risk assessment needs to be done in urban areas.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…It has been demonstrated that, in the process of coal mining, the treatment and storage of coal provided the basic conditions for the release of PAHs into the environment [4][5][6][7][8][9]. For example, PAHs in coal and coal waste could be leached into the mine water [10] and then enter into the aquatic environment with the discharge of mine water [11].…”
Section: Introductionmentioning
confidence: 99%
“…erefore, the occurrence of PAHs in surface water nearby the coal mining area has attracted lots of attention recently [5,9,12,13]. However, studies on concentrations, sources, and ecological risk of PAHs in surface water of rivers located in or nearby the coal mining area are generally limited at present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high concentrations of PAHs detected in leaves of shrubs near coal-fired power plants could pinpoint conspicuous air contamination [13]. A number of reports have shown that coal tar is an important source of urban PAH and that high PAH concentrations in soil and water have been detected in the vicinity of coal or coal gangue dumps [14][15]. Obvious differences have also been observed in the PAH content of soil in the northern and southern regions of China.…”
mentioning
confidence: 99%